Magnetohydrodynamic (MHD) Natural Convection Flow of Titanium Dioxide Nanofluid Inside 3D Cavity Containing a Hot Block: Comparative with 2D Cavity - Moderres, Mourad; Boutra, Abdelkader; Kherroubi, Seddik; Öztop, Hakan Fehmi; Benkahla, Youb Khaled (Amer Scientific Publishers, 2023)
The natural convection of TiO2-Water-Nanofluid in a cubic cavity, containing a hot block under the influence of the magnetic field was studied numerically. The verticals walls are cold, the bottom wall is hot and the other walls (top, front and rear) are adiabatic. This work aims to visualize the importance of taking into account the three-dimensionality of the flow in the presence of magnetic field as well as the impact of the addition of nanoparticles on heat exchange rate evolution. The governing equations are solved using the finite volume method and the SIMPLER algorithm is used for pressure-velocity coupling. The problem was simulated at different Rayleigh numbers (103 < Ra < 106), Hartmann numbers (0 < Ha < 90) and inclination angles of the magnetic field (0 < (.0 < 135 degrees) as well as nanoparticles volume fraction (9 = 0%, phi = 5%) with fixed Prandtl number (Pr = 7). The thermal conductivity and dynamic viscosity of the nanofluid are estimated by taking into account temperature-dependent properties, using Corcione's correlations. Based on the cooling optimization of IP: 203.8.109.20 On: Tue, 09 May 2023 06:41:22 cold walls along with comparative analysis betwen 3D caviy and 2D cavity, the obtained results show that Copyright: American Scientific Publishers the buoyancy force enhances the heat exchange, while the magnetic field produces opposite effects. When Delivered by Ingenta the buoyancy force is dominated, the intensification of heat transfer becomes large, compared to the case where conduction is dominant. The qualitative difference between a 3D and 2D configuration is remarkable for higher Ra, and becomes smaller when the magnetic field is applied horizontally or vertically with relatively high intensity. But, quantitatively, the 3D flow is far from being considered as a 2D flow for all pertinent parameters control. Finally, adding nanoparticles enhances heat transfer for both configurations, the best transfer rate is obtained for w = 0.
Keywords: Magnetoconvection; Nanofluid; 3D and 2D Configurations; Hartmann Number; Thermal Conductivity